Онто-гносеологічні засади актуалізації волі у правовій реальності - Трофімова, Л.В.; Савчук, С.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Рассматриваются онто-гносеологические основания актуализации воли в правовой реальности: воля как неотъемлемый атрибут человеческого способа бытия пронизывает всё право; через субъекта
и в субъекте актуализируется воля в правовой реальности. The article unfolds ontho-gnoseological foundations of the actualization of the will in legal reality: will as
an inalienable attribute of the human method of being is throughout all law; the will is being actualized into
the legal reality throught the the subject and within the subject.